100 things you should know about Kings & Queens - Macdonald, Fiona; Miles Kelly Publishing; Steele, Philip (Essex: Miles Kelly Publishing Limited., 2004)
This title presents in fascinating detail an array of British monarchs from across the ages. Artwork throughout illustrates the life and times of fiery Queen Boudicca, the exploits of Richard III and the glorious reign of Elizabeth I.
Keywords: Kings and Queens